PENGARUH CSR DAN EFEK KARAKTERISTIK PERUSAHAAN TERHADAP TAX AVOIDANCE DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MODERASI - Andi Nabila Meutia Rafika,; Bulutoding, Lince; Syariati, Namla Elfa (ISAFIR: Islamic Accounting and Finance Review, 2022)
Abstrac, Tax avoidance is legal in the eyes of the law, but it is unethical behavior when viewed from an ethical perspective. Companies that do tax avoidance are considered socially irresponsible. Disclosure of Corporate Social Responsibility (CSR) in Indonesia is disclosed in sustainability reporting as an additional report in addition to the company's annual financial statements as required by the government. This study uses a causal comparative research approach. The object of the study was the financial statements of 60 companies listed in the Jakarta Islamic Index (JII) for the 2015-2019 period. Corporate Social Responsibility (CSR) has a negative and significant effect on Tax avoidance. The size of the Company has a positive and significant effect on tax avoidance. Multinational Company has a positive and significant effect on tax avoidance. The Company's Financial Performance does not moderate the relationship between Corporate Social Responsibility (CSR) and tax avoidance. The Company's Financial Performance does not moderate the effect of the Company Size on tax avoidance. The Company's Financial Performance moderates the relationship between the company's multinational variable and the Tax avoidance variable. Abstrak, Tax avoidance atau penghindaran pajak merupakan hal yang legal di mata hukum, namun merupakan perilaku yang tidak etis jika dilihat dari perspektif etika. Perusahaan yang melakukan tax avoidance dianggap tidak bertanggung jawab secara sosial. Pengungkapan Corporate Social Responsibility (CSR) di Indonesia diungkapkan dalam sustainability reporting sebagai laporan tambahan selain laporan keuangan tahunan perusahaan sesuai yang disyaratkan pemerintah. Penelitian ini menggunakan pendekatan kausal komparatif (causal comparative research). Objek penelitian adalah laporan keuangan 60 perusahaan yang terdaftar dalam Jakarta Islamic Index (JII) periode 2015-2019. Corporate Social Responsibility (CSR) berpengaruh negatif dan signifikan terhadap Tax avoidance. Ukuran Perusahaan berpengaruh secara positif dan signifikan terhadap tax avoidance. Multinational Company berpengaruh positif dan signifikan terhadap tax avoidance. Kinerja Keuangan Perusahaan tidak memoderasi hubungan antara Corporate Social Responsibility (CSR) dengan tax avoidance. Kinerja Keuangan Perusahaan tidak memoderasi pengaruh Ukuran Perusahaan terhadap tax avoidance. Kinerja Keuangan Perusahaan memoderasi hubungan antara variabel multinational company dengan variabel Tax avoidance.